Conversion factors between human and automatic readouts of CDMAM phantom images of CR mammography systems. (31st August 2016) - Figl, Michael; Homolka, Peter; Osanna-Elliott, Angelika; Semturs, Friedrich; Kaar, Marcus; Hummel, Johann
Abstract: In mammography screening, profound assessment of technical image quality is imperative. The European protocol for the quality control of the physical and technical aspects of mammography screening (EPQCM) suggests using an alternate fixed choice contrast-detail phantom-like CDMAM. For the evaluation of technical image quality, human or automated readouts can be used. For automatic evaluation, a software (cdcom ) is provided by EUREF. If the automated readout indicates unacceptable image quality, additional human readout may be performed overriding the automated readout. As the latter systematically results in higher image quality ratings, conversion factors between both methods are regularly applied. Since most image quality issues with mammography systems arise within CR systems, an assessment restricted to CR systems with data from the Austrian Reference Center in the mammography screening program has been conducted. Forty-five CR systems were evaluated. Human readouts were performed with a randomisation software to avoid bias due to learning effects. Additional automatic evaluation allowed for the computation of conversion factors between human and automatic readouts. These factors were substantially lower compared to those suggested by EUREF, namely 1.21 compared to 1.62 (EUREF UK method) and 1.42 (EUREF EU method) for 0.1 mm, and 1.40 compared to 1.83 (EUREF UK) and 1.73 (EUREF EU) for 0.25 mm structure size, respectively. Using either of these factors to adjust patient dose in order to comply with image quality requirements results in differences in the dose increase of up to 90%. This necessitates a consensus on their proper application and limits the validity of the assessment methods. Clear criteria for CR systems based on appropriate studies should be promoted.